2000
DOI: 10.1007/s00585-000-0416-0
|View full text |Cite
|
Sign up to set email alerts
|

A survey of magnetopause FTEs and associated flow bursts in the polar ionosphere

Abstract: Abstract. Using the Equator-S spacecraft and Super-DARN HF radars an extensive survey of bursty reconnection at the magnetopause and associated¯ows in the polar ionosphere has been conducted. Flux transfer event (FTE) signatures were identi®ed in the Equator-S magnetometer data during periods of magnetopause contact in January and February 1998. Assuming the e ects of the FTEs propagate to the polar ionosphere as geomagnetic ®eld-aligned-currents and associated Alfve n-waves, appropriate ®eld mappings to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 53 publications
1
41
1
Order By: Relevance
“…Parallel currents flowing on the flanks of the flow burst have been modelled (Southwood, 1987;Lockwood et al, 1990Lockwood et al, , 2001 and observed . Results of detailed case studies of corresponding ionospheric and magnetopause features (Elphic et al, 1990;Neudegg et al, 1999Neudegg et al, , 2000 have been complemented by statistical studies of the location, occurrence, and relation to IMF B y of ionospheric flow bursts (e.g., McWilliams et al, 2000). Provan et al (1998, and Thorolfsson et al (2000) have used radars and optical observations to determine the size, shape, velocity and recurrence rate of the ionospheric signatures of FTEs.…”
Section: Flux Transfer Eventsmentioning
confidence: 99%
“…Parallel currents flowing on the flanks of the flow burst have been modelled (Southwood, 1987;Lockwood et al, 1990Lockwood et al, , 2001 and observed . Results of detailed case studies of corresponding ionospheric and magnetopause features (Elphic et al, 1990;Neudegg et al, 1999Neudegg et al, , 2000 have been complemented by statistical studies of the location, occurrence, and relation to IMF B y of ionospheric flow bursts (e.g., McWilliams et al, 2000). Provan et al (1998, and Thorolfsson et al (2000) have used radars and optical observations to determine the size, shape, velocity and recurrence rate of the ionospheric signatures of FTEs.…”
Section: Flux Transfer Eventsmentioning
confidence: 99%
“…For such small‐scale spatial and temporal features to be accurately represented in such convection maps, extensive radar backscatter coverage is required as an input [ Ruohoniemi and Baker , 1998]. Intervals with such data coverage have recently revealed far more spatial and temporal structuring of the cusp convection [e.g., Neudegg et al , 2000; McWilliams et al , 2001]. The combination of multisatellite data with such ionospheric convection maps will form a future study.…”
Section: Conclusion and Summarymentioning
confidence: 99%
“…Of the 807 FTEs in our database, 638 were observed in the magnetosheath (79 %) but only 169 in the magnetosphere (21 %). For comparison, 75 % of the low-latitude Equator-S events reported by Neudegg et al (2000) occurred in the magnetosheath, whereas only ∼69 % of the low-latitude ISEE-1/2 events reported by Rijnbeek et al (1984) and Kuo et al (1995) occurred in the magnetosheath. Figure 6 presents a histogram of all the event amplitudes, as measured by the peak-to-peak variation in Bn.…”
Section: Statistical Surveymentioning
confidence: 90%